Language teaching and language standardization - Casambre, Nelia G. (Education quarterly.)
This paper aims to determine what language teaching is in this country. It shall point out its unique features and the confusion and problems encountered by the language teacher attendant to the equally confusing status of language instruction in our country today. It shall deal with the standardization and the role of language teaching in this crucial national issues it will wind up some recommendations on how language teaching could be of help in standardization and some rejoinders to teachers and educationists of their responsibilities as disseminators of language